Dietary analysis and nutritional counselling for caries prevention in dental practise: a pilot study. (28th June 2017) - Hayes, MJ; Cheng, B; Musolino, R; Rogers, AA
Abstract: Background: Dental practitioners agree that dietary counselling is essential for caries prevention; however, they provide advice infrequently due to a lack of confidence and competence. This study aimed to improve practises through an online training module exploring the use of a brief counselling method, and a diet assessment of caries risk form. Methods: Dental practitioners (N = 41) completed a survey on current practises and confidence in providing dietary advice, followed by an online training module. Ten practitioners were involved in recruiting patients, eliciting a diet assessment of caries risk, and using brief counselling techniques with these patients. Patients were followed up at 6 months for a risk assessment review. Dental practitioners also completed a 6‐month follow‐up survey exploring changes in confidence and perceived barriers. Results: Dental hygienists' confidence improved significantly following the intervention ( P < 0.025). Patients showed a significant reduction in high‐risk behaviour pertaining to quantity and timing of sugar intake, and significant trends in improvement of behaviours relating to frequency, exposure time and drinking style ( P < 0.05). Conclusions: It appears that a simple online learning module can improve hygienists' confidence in dietary advice provision, and have a positive impact on patient behaviour change, within a relatively short time‐frame.